Tone from the Top and internal audit: Analysis of the SUS governance environment - Hohenfeld Macedo dos Santos, Rafael; Demarche Minatti Ferreira, Denize; Martins Dias Maragno, Lucas; Mussoi Ribeiro, Alex (Advances in Scientific and Applied Accounting, 2023)
Objetivo: This research examines the perceptions of the internal audit staff of the Unified Health System (SUS), in relation to the governance structure and Tone at the Top (TaT) of the Ministry of Health (MS). Method: A survey strategy was used. Data were collected through a survey applied to all employees working in the internal audit unit, AudSUS (formerly Denasus), and were divided into two dimensions: SUS control environment and audit and TaT, both at the federal level. Data collection resulted in 233 complete responses, representing 54% of the invitations sent. The dimensions were measured using multiple five-point scales. Several quantitative techniques were used for data analysis, including frequencies, percentages, means and deviations (for continuous variables), Cronbach’s alpha, and Cramer V. Results: From the respondents’ point of view, weaknesses were observed in the performance of the roles of governance actors, as well as in the organizational control environment and in the independence and autonomy of internal audit. Also noteworthy is the low level of maturity of the integration between the internal audit unit and governance stakeholders. Our findings point to a misalignment between top management and internal audit, which affects communication and affects the autonomy and effectiveness of the internal audit unit’s work. Contributions: Our study contributes to the improvement of SUS governance and internal audit in the public sector, particularly in the Ministry of Health.